Artificial intelligence reflections in philosophy, theology, and the social sciences - Göcke, Benedikt Paul 1981-; Rosenthal-von der Pütten, Astrid 1980- (Leiden Paderborn Brill, mentis, 2020)
Front Matter --Copyright page --Introduction /Benedikt Paul Göcke and Astrid Rosenthal-von der Pütten --Consciousness --Conscious, Thinking, and Intelligent Machines? /Tobias Müller --Deus Malignus - The Digital Rehabilitation of Deception /Walther Ch. Zimmerli --Artificial Intelligence of the Human Mind /Daniel Neumann --When Robots (pretend to) Think /Davide Ghiglino and Agnieszka Wykowska --Revisiting the Dancing-Qualia Argument for Computationalism /Stefan Reining --Superintelligence --Will Superintelligence Take Over? /Kilian Karger --Why Artificial Intelligence is a Matter of Design /Andreas Theodorou --Between Epistemic Progress and Existential Risk Minimization /Julia Alessandra Harzheim --Ethics --Current Challenges in Ethics of Artificial Intelligence or: Old Wine in New Bottles /Leonie Seng --Is Utilitarianism Entirely Useless for Self-Driving Car Ethics? /Vanessa Schäffner --The Car's Choice: Illusions of Agency in the Self-Driving Car Trolley Problem /Rebecca Davnall --Why Machines That Talk Still Do Not Think, and Why They Might Nevertheless be Able to Solve Moral Problems /Lukas Brand --Robots --Could Artificial General Intelligence be an End-In-Itself? /Benedikt Paul Göcke.
Can Robots Have Dignity? /Carmen Krämer --The Right(s) Question: Can and Should Robots Have Rights? /David J. Gunkel --Image, Servitude, Partnership /Gábor L. Ambrus --From Experiential to Existential Questions /Diana Löffler, Swantje Luthe, Jörn Hurtienne, and Ilona Nord --Robots and the Complexity of Everyday Worlds /Andreas Bischof and Arne Maibaum --Taught by Technology /Scarlet Siebert --Society --Artificial Intelligence and Polygenic Scoring /Johannes Grössl --Could Machines Replace Human Scientists? /Jan G. Michel --Organizational and Societal Implications of the Adoption of Machine Invention Systems /Dragos-Cristian Vasilescu and Michael Filzmoser --Back Matter --About the Authors --Index.
This book discusses major issues of the current AI debate from the perspectives of philosophy, theology, and the social sciences: Can AI have a consciousness? Is superintelligence possible and probable? How does AI change individual and social life? Can there be artificial persons? What influence does AI have on religious worldviews? In Western societies, we are surrounded by artificially intelligent systems. Most of these systems are embedded in online platforms. But embodiments of AI, be it by voice or by actual physical embodiment, give artificially intelligent systems another dimension in terms of their impact on how we perceive these systems, how they shape our communication with them and with fellow humans and how we live and work together. AI in any form gives a new twist to the big questions that humanity has concerned herself with for centuries: What is consciousness? How should we treat each other - what is right and what is wrong? How do our creations change the world we are living in? Which challenges do we have to face in the future?
"The conference "When Robots Think - Interdisciplinary Views on Intelligent Automation", held in Münster (Germany) in November 2018 ..." - Einleitung
Keywords: Artificial Intelligence; Konferenzschrift -- 2018 -- Münster